Multi-objective optimisation of a permanent magnet flux-switching motor by combined parameter sensitivities analysis with non-linear varying-network magnetic circuit method - Zhu, Xiaoyong; Jian, Yanhong; Xiang, Zixuan; Fan, Deyang; Yang, Minjian (IET electric power applications, 2019)
In this study, a new sensitivity analysis based on non-linear varying-network magnetic circuit (VNMC) method is proposed for an outer-rotor I-shaped permanent magnet flux-switching motor. By integrating concept of sensitivity analysis into the non-linear VNMC method, the whole design efficiency can be improved effectively by using the comprehensive sensitivity method and sequential non-linear programming algorithm. In the optimisation process, two design objectives are selected, including machine output torque and torque ripple. Based on the sensitivity analysis, the parameters possessing the significant influence on the design objectives can be selected purposely, thus the overall amount of calculation is obviously reduced. After the determination of the sensitive parameters, the rest of optimisation can be realised efficiently by the non-linear VNMC method. Finally, a prototype motor is manufactured and tested. Both theoretical analysis and experimental results confirm the effectiveness of the proposed method.